Submaximal intensity periods in game-based drills vs. match demands in professional football - Caro, Edu; Lapuente-Sagarra, Manuel; Caparrós, Toni; Campos-Vázquez, Miguel Ángel; Pajón, David (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study aimed to examine the occurrence of submaximal intensity periods (SubMIPs) across several game-based drills according to area per player (ApP) and drill objective, and to compare them with values recorded in competitive matches.MethodsFourteen professional football players participated. Data from 1,558 game-based drills events and 247 competitive match records were analyzed using GPS technology. SubMIP events defined as efforts exceeding 85% of each player's 1 min maximal intensity period (MIP) per variable, were calculated for distance, acceleration density (AccDens), high-speed running (HSR), sprints, high metabolic load distance (HMLD), and mean metabolic power (MetPow). Game-based drills were categorized by ApP (<75 m2, 75–150 m2, >150 m2) and objective (possession, four small goals, regular goals).ResultsSubMIP AccDens events were more frequent in game-based drills than in matches, especially in possession drills with smaller ApP. Distance and MetPow events increased with ApP, but none of the game-based drills fully replicated match-level frequencies. HSR, HMLD, and sprint events occurred significantly more often in matches than in any drill.ConclusionsApP and drill objective strongly influence physical demands. Although game-based drills do not replicate all match demands, they can be tailored to target specific SubMIP variables. The SubMIP approach provides valuable insights into near-maximal efforts and supports the design of training sessions that optimise player conditioning through repeated high-intensity exposures.